Construction of An Automatic Power Switch using Infrared Motion Sensor - Nwoye, C. D.; Usikalu, M. R.; Babarimisa, I. O.; Achuka, J. A.; Ayara, W. A. (Journal of Informatics and Mathematical Sciences, 2017)
In public and private institutions the problem of switching off light and other appliances wherever it is not needed is a concern. In Covenant University, the issue led to various rules that try to limit the way light is being used in the halls of residence, classrooms and other buildings. The main aim of this project is to conserve energy. This project presents the construction of a power control system which can detect the approach of a person, and then turn the power of a room on. The project involves four stages: the power supply stage, the sensor stage, the arduino stage and the switching mechanism stage. The power supply stage involves the supply of power to the arduino and the sensor. The sensor stage consist the passive infrared sensor which is the core part of the project. It detects the radiated heat energy from a person and converts the energy to an electrical signal which is sent to the arduino for processing. The arduino then processes the signal and sends a specific voltage to the relay that actuates the power switch to on. When nobody is detected the power is turned off. Conclusively, the constructed energy control system prevents energy wastage in the lecture halls, classrooms and other buildings.